Analisis Potensi Batuan Trass (Pozolan) Untuk Bahan Baku Pembuatan Semen di PT. Bumi Hijau Citra Andalas Site Batu Hampar, Kecamatan Akabiluru, Kabupaten Lima Puluh Kota, Provinsi Sumatera Barat - Fajri Hafiz Nurzam; Yoszi Mingsi Anaperta (Journals Mining Engineering : Bina Tambang, 2020)
Abstract. This research was conducted at PT Bumi Hijau Citra Andalas site Batuhampar Akabiluru district fifty district cities. In this study, the method used is descriptive method that is a research method that evaluates the condition of the object as it is in a situation that is being the object of research. This research is more focused on pozolan quality analysis by testing sambal in the laboratory using XRF with a total sample of 7 sampling points (description of sampling by drilling)After being analyzed, it can be concluded that the average values of (Fe2O3), (SiO2), (Al2O3) obtained in the polls of laboratory test results using XRF are (2.590%), (70.107%), (14.297%) In this test, all of the samples analyzed almost all met the standard according to ASTM C618-92a, only 1 sample did not meet the standard so that when examined in quality the pozolan really met the ASTM C618-92a standard, therefore it was seen in quantity, pozolan resources exist in the area is very potential.Keywords: Pozolan, Kab. 50 cities, Quality Analysis, Cement Raw Materials